The role of beliefs about the impact of illness on fertility and close relationships for psychopathological symptoms in women treated for hypothyroidism. Issue 12 (27th June 2020) - Wytrychiewicz, Kinga; Pankowski, Daniel; Janowski, Konrad; Benoit, Charles E.; Bargiel‐Matusiewicz, Kamilla; Pisula, Ewa; Walicka, Magdalena
Abstract: Objective: As demonstrated in a pilot study, hypothyroidism has a highly stressful impact on some areas of functioning. This study aims to evaluate the connection between illness‐related beliefs (IRBs) and the impact of hypothyroidism on fertility and close relationships, which were the strongest stressors, and the level of depressive, anxiety, and anger symptoms. Methods: Two hundred and thirteen women being treated for hypothyroidism took part in an online survey and completed the modified Hospital Anxiety and Depression Scale, Hypothyroidism Symptoms Severity rating scales, and a measure of IRBs. Other relevant clinical data were also collected. Result: Mean levels of thyroid‐stimulating hormone indicated that the women were euthyroid. Four groups of participants were identified based on IRBs. The group holding a strong IRB about the negative impact of illness only on close relationships scored significantly higher on depressive symptoms than women in the other groups. The group holding strong IRBs about the negative impact of illness on both close relationships and fertility scored significantly higher on anxiety symptoms than the women in the other groups. Regression analysis showed that IRBs about the negative impact of hypothyroidism predicted anxiety, depressive, and anger symptoms. Conclusions: Negative IRBs about the impact of illness on fertility and close relationships contribute to increased levels of emotional distress symptoms in women being treated for hypothyroidism.